2014
DOI: 10.2527/jas.2014-8086
|View full text |Cite
|
Sign up to set email alerts
|

The consequence of level of nutrition on heifer ovarian and mammary development1,2

Abstract: Replacing cows in the herd is second only to nutrition as the single greatest input cost in cow/calf beef production. The increased availability of cereal grains for feeding livestock has allowed replacement heifers to enter the production system at younger ages. Many heifer development programs feed to ensure heifers reach puberty before the time that they are mated to calve at 2 yr of age. Nutrition level during development has been associated with altered milk production and stayability. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our results agree with those described by Freetly and Cundiff (1998) over a diverse group of beef breeds, who did not observe any difference in milk production traits between heifers raised on different planes of nutrition. Moreover, Freetly et al (2014) could not demonstrate that modifying peripubertal nutrition could modify DNA methylation in the mammary gland and consequently alter milk production. Table 3.…”
Section: Productive Performancementioning
confidence: 87%
“…Our results agree with those described by Freetly and Cundiff (1998) over a diverse group of beef breeds, who did not observe any difference in milk production traits between heifers raised on different planes of nutrition. Moreover, Freetly et al (2014) could not demonstrate that modifying peripubertal nutrition could modify DNA methylation in the mammary gland and consequently alter milk production. Table 3.…”
Section: Productive Performancementioning
confidence: 87%
“…Restricting weight gain in early gestation in pregnant cows reduces the number of antral follicles in heifers born to those restricted dams (Mossa et al, 2013). Reducing rate of gain during a few weeks before expected puberty increases the number of primordial follicles near first breeding (Freetly et al, 2014;Amundson et al, 2015). Inflammation associated with disease reduces the number of primordial follicles (Bromfield and Sheldon, 2013).…”
Section: Understanding Epigenetic Effectsmentioning
confidence: 99%
“…The most likely mechanisms are either 1) decreased proliferation of primordial germ cells in utero leading to fewer primordial follicles being formed, or 2) accelerated depletion of the primordial follicles in the ovaries of the heifers with primparous dams leading to fewer primordial follicles at a year of age. There is certainly evidence for either of these, because both the maternal environment during gestation (Evans et al, 2012;Mossa et al, 2013;Akbarinejad et al, 2017) and nutritional status during the first year of life (Freetly et al, 2014;Amundson et al, 2015) influence the size of the ovarian follicle reserve in heifers. Further studies evaluating fetal ovaries and ovaries collected between birth and a year of age will be necessary to determine the exact timing of the divergence in primordial follicle numbers.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that heifer born to mature beef cows had greater circulating concentrations of anti-Müllerian hormone (AMH), a blood marker of size of the ovarian reserve, and greater fertility than heifers with primiparous dams (Akbarinejad et al, 2018). While both number of antral follicles (Cushman et al, 1999) and circulating concentrations of AMH (Ireland et al, 2008) are generally correlated to the size of the ovarian reserve, there are studies where differences in numbers of primordial follicle do not result in differences in numbers of antral follicles (Freetly et al, 2014;Amundson et al, 2015). It, therefore, is important to perform the histological evaluation to clearly identify whether there are differences in the size of the ovarian follicle reserve between heifers with primiparous dams as compared with those from multiparous dams as a first step in understanding the mechanisms behind these differences.…”
Section: Introductionmentioning
confidence: 99%